PENGARUH PENERAPAN PEMBELAJARAN ONLINE, MOTIVASI BELAJAR, DAN KREATIVITAS TERHADAP HASIL BELAJAR SISWA TKJ DI SMK NEGERI 8 JENEPONTO - Rohani; Muhammad Yahya; Bakhrani A. Rauf (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study is a quantitative research with ex-post facto research method. The study aims to examine the influence of the implementation of online learning, learning motivation, and creativity on the learning outcomes. The total population was 58 people and the samples obtained were 58 people taken by using non-probability sampling or saturated sampling technique. Data collection employed documentation and questionnaire. The prerequisite test employed the normality test, linearity test, and multicollinearity test. The hypothesis testing employed simple linear regression and multiple linear regression. The results of the study indicate that (1) the online learning is in high category, (2) the students' learning motivation is in moderate category, (3) the creativity is in moderate category, (4) the learning outcomes in Network System Administration subject are in good criteria, (5) there is an influence of online learning on learning outcomes in Network System Administration subject of TKJ at SMKN 8 Jeneponto. The test result shows that the value of sig. of 0.020 < 0.05 with a contribution of 9.3%, (6) there is an influence of learning motivation on learning outcomes in Network System Administration subject of TKJ at SMKN 8 Jeneponto. The test result shows that the value of sig. of 0.049 < 0.05 with a contribution of 6.8%, (7) there is an influence of creativity on learning outcomes in Network System Administration subject of TKJ at SMKN 8 Jeneponto. The test result shows that the value of sig. of 0.032 < 0.05 with a contribution of 8.0%, and (8) there is an influence between online learning, learning motivation, and creativity on learning outcomes in Network System Administration subject of TKJ at SMKN 8 Jeneponto. The test result shows the value of sig. of 0.019 < 0.05 with a contribution of 16.6%. Therefore, the research hypothesis is accepted.